Pathways for Expressing Contemporary Chinese Christian Public Values: Perspectives on the Public Nature of Religious Belief and Its Recognition - LI, Xiangping (Journal of Research for Christianity in China (JRCC), 2025)
In the construction and the requirements of the modern civil society, reli- gious theology, religion and its practice, corresponding to the modern society has gradually become a public demand. While the Christian theological thought, belief and practice mean- ing, can have extremely method, go beyond the inherent faith groups of public values. How to construct a Chinese Christian public value realization and the full expression of public path? And the expression pattern of practical investigation of morphological and Chinese Christian faith, should be the basic premise of public value of Christian view of china. Chinese Christian Church "Hall -" mode, it is Chinese Christian party pattern, it is based on the "Hall - point", the Christian faith groups, mainly around the two center to expand. Neither the church, nor the government administration directly. Therefore, not only is the church - Christian management mode, all over the Christian understanding of doctrine, in fact is a symbol of the Chinese Christian localization development mode.